Toxicity study of antibiotics to the common duckweed (Lemna minor) - Aubakirova, B.N.; Boxall, A.B.A.; Beisenova, R.R. (Fundamental and Experimental Biology, 2017)
The following paper demonstrates the results of the scientific study of toxicity effect of five antibiotics as amoxicillin, clarithromycin, azithromycin, sulfamethoxazole and oxytetracycline hydrochloride to the growth of common duckweed Lemna minor. It was defined that the half maximal effective concentration of five previously mentioned antibiotics was equal to 27.8, 15.29, 28.77, 3.67 and 13.51 mg/L respectively. Overall, the results of the study showed that the duckweed was sensitive to all selected compounds, however sulfamethoxazole was the most toxic to these species. The present study is significant, as currently people consume antibiotics in huge amount. Their occurrence on the surface was found around the world and their effect to the environment and living organisms are not fully studied yet. The recent studies show that in most cases they have adverse effect to the aquatic microorganisms.